THE IMPLEMENTATION OF ROLE PLAY TECHNIQUE IN TEACHING SPEAKING (AN EXPERIMENTAL STUDY TO THE FIRST YEAR STUDENTS OF SMP N 8 NAGAN RAYA) - ZA, Maulizan (STKIP Bina Bangsa Getsempena Banda Aceh, 2016)
This study study aimed to examine whether there is a significant difference in the speaking mastery of students between those who are taught using role play and traditional technique. The subjects of the study were all students of First grade students of SMPN 8 Nagan Raya. The population in this research is the first grade students which consist of 42 students from two classes. In this research, the researcher does not take any sample. The subject of this researcher is the population; 42 students. The population was divided into two groups; 21 students were experimental group and 21 students were control group. The data collected through pre-test and post-test. The pre-test was given to control and experimental group. The scores were obtained to know whether the means of the two groups were not significantly different. From the result of data analysis on the studentsâ score in pre-test found that the mean score of experimental group was 50.71, the mean score of control group was 49.61, the t-value was 0.64, and the t-critical was 1.684. From the result above, it is found that there is no significant difference between two mean because t-value is smaller than t-critical. Therefore, it can be concluded that experimental and control groups had same English ability at the time of the test. The result of data analysis on the studentsâ score of post-test, it was found that the mean score of experimental group was 70.14, the mean score of control group was 54.67, t-value was 18.31 and t-critical was 2.021. From the result above, it is found that there is a significant difference between two means because t-value is greater than t-critical. Therefore, it can be concluded that the students who were taught by using role play gave better result compared the using speaking through traditional technique.Â Keywords: Role Play, Speaking, Mastery